Micrococcal Nuclease Treatment of Bacteriophage Heads Alters the Right-Hand Cohesive End of Lambda Deoxyribonucleic Acid - Gillin, Frances D. (1972)
Isolated bacteriophage lambda heads were exposed to micrococcal nuclease prior to addition of the phage tail. The deoxyribonucleic acid (DNA) was extracted from the heads and sheared to half-molecules whose cohesive ends were annealed to normal lambda DNA half-molecules. Melting curves of each of the cohered halves indicated that only the right-hand termini are altered by nuclease treatment.